2020
DOI: 10.5006/3642
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition of Brazing Cu-Ag Alloy with 1,2,3-Benzotriazole and 2,5-Dimercapto-1,3,4-Thiadiazole

Abstract: Adsorption and inhibition behavior of 1,2,3-benzotriazole (BTA) and 2,5-dimercapto-1,3,4-thiadiazole (DMTD) on brazing Cu-Ag alloy was studied in deionized water using potentiodynamic polarization measurement, adsorption isotherm investigation and X-ray photoelectron spectroscopy (XPS). Pure Ag and pure Cu were included to investigate the mere effect of each component on the alloy’s behavior. Results show better inhibition of DMTD for Ag and BTA for Cu, both by chemisorption. BTA was found to follow Langmuir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Tafel curve is a typical method to investigate the corrosion behavior of metal, where corrosion current ( I c ) represents corrosion rate and self‐corrosion potential ( E c , at which the corrosion current is smallest) represents corrosion tendency. [ 33 ] As shown in Figure 2d, the major difference in Tafel curves appears in the anodic section (right section), indicating that MBT mainly affects the anodic oxidation process of Ag film. In anodic region, the corrosion current of Ag film is always twice higher than that of MBT/Ag film, indicating a much faster corrosion rate of Ag film.…”
Section: Resultsmentioning
confidence: 98%
“…Tafel curve is a typical method to investigate the corrosion behavior of metal, where corrosion current ( I c ) represents corrosion rate and self‐corrosion potential ( E c , at which the corrosion current is smallest) represents corrosion tendency. [ 33 ] As shown in Figure 2d, the major difference in Tafel curves appears in the anodic section (right section), indicating that MBT mainly affects the anodic oxidation process of Ag film. In anodic region, the corrosion current of Ag film is always twice higher than that of MBT/Ag film, indicating a much faster corrosion rate of Ag film.…”
Section: Resultsmentioning
confidence: 98%
“…Various isotherms were tested with the parameters calculated from the weight loss data and it is found that the Langmuir isotherm is best suited isotherm for the adsorption for SPS inhibitor for mild steel surface at 100ppm concentration of inhibitor at 0.5M HCl at 35°C for 3h duration reported in Figure 3. It has been found after the examination of the Figure 3 that the value of regression coefficient (R 2 ) is about to be unity, represents the finest definition of adsorption activity by isothermal adsorption by Langmuir [26,42,51].…”
Section: Adsorption Studiesmentioning
confidence: 94%
“…During the path changes, both cathodic and anodic reactions were shown to be affected by the inhibitor. However, the impact is more prominent compared to that in anodic polarization plots in cathodic polarization plots [42,51]. Since the measurements βc and βa in Tables 3 change with an increase in the inhibitor concentration, a high βc value indicates that the cathodic reaction is more delayed than the anodic [52].…”
Section: Polarization Measurementsmentioning
confidence: 94%
See 1 more Smart Citation
“…Adsorption of drug inhibitor molecules causes polarization resistance Rp, which increases with the number of adsorbed molecules. Furthermore, the adsorbed inhibitor film reduces capacitance at the metal-solution interface as a result of a reduction in the dielectric constant between metal and electrolyte and/or an improvement in thickness of metal (48)(49)(50).…”
Section: Tafel Polarizationmentioning
confidence: 99%